2019
DOI: 10.1029/2018jb016914
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rheology on the Transition From Stick‐Slip to Creep in a Semibrittle Analog

Abstract: Faults can release energy via a variety of different slip mechanisms ranging from steady creep to fast and destructive earthquakes. Tying the rheology of the crust to various slip dynamics is important for our understanding of plate tectonics and earthquake generation. Here we propose that the interplay of fractures and viscous flow leads to a spectrum between stick‐slip and creep. We use an elasto‐visco‐plastic rock analog (Carbopol U‐21) where we vary the yield stress to investigate its impact on slip dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Such classical wing cracks are typically found in laboratory experiments and as subsidiary cracks in nature (e.g. Lee et al, 2016;Birren and Reber, 2019;Mutlu and Pollard, 2008;Willemse and Pollard, 1998). In the following we briefly attempt to link our model observations with the theory of wing cracks and normal and reverse faults in nature.…”
Section: Wing Crack Transition and Relation To Normal And Reverse Faumentioning
confidence: 87%
“…Such classical wing cracks are typically found in laboratory experiments and as subsidiary cracks in nature (e.g. Lee et al, 2016;Birren and Reber, 2019;Mutlu and Pollard, 2008;Willemse and Pollard, 1998). In the following we briefly attempt to link our model observations with the theory of wing cracks and normal and reverse faults in nature.…”
Section: Wing Crack Transition and Relation To Normal And Reverse Faumentioning
confidence: 87%
“…Nonetheless, the dominant shear component alludes to a transition or an approximation to a wing crack rather than the development of a classical wing crack. Such classical wing cracks are typically found in laboratory experiments and as subsidiary cracks in nature (e.g., Lee et al, 2016;Birren and Reber, 2019;Mutlu and Pollard, 2008;Willemse and Pollard, 1998). In the following we briefly attempt to link our model observations with the theory of wing cracks and normal and reverse faults in nature.…”
Section: Wing Crack Transition and Relation To Normal And Reverse Faumentioning
confidence: 90%
“…However, changes in other frictional parameters or material parameters (e.g., shear modulus) with plastic strain are not taken into account in our simulations despite the fact that they can be expected in natural fault systems. Our model is a simplification in that it ignores anisotropy, poroelasticity and dilatant volume changes, which are typically observed in natural faults (e.g., Woodcock et al, 2007;Brace et al, 1966;Peacock and Sanderson, 1992;Rawling et al, 2002). Our choice of parameters results in a Poisson's ratio of 0.125.…”
Section: Width Of the Off-fault Fanmentioning
confidence: 99%
“…Velocity‐strengthening parts of a subduction interface can produce an SSE by damping an otherwise unstable rupture initiating in velocity‐weakening material (Luo & Ampuero, ; Skarbek et al, ). Analog models show that slow stick‐slip events can occur in a macroscopically homogeneous viscoplastic material likely due to reorganization of microgel force chains (Birren & Reber, ; Reber et al, ). These analog models showed that microscopically these events are related to reorganization of force chains, while macroscopically they correspond to episodic opening of tensile fractures, which grade into shear fractures and viscous deformation accommodating overall simple shear.…”
Section: Introductionmentioning
confidence: 99%